Not I: Rosalind Krauss and Jasper John's ironies (Palíndromo, 2021)
The text proposes a reading of Rosalind Krauss’ two essays on the work of the painter Jasper Johns. It starts from Krauss’ antithetical perspectives on Johns’ paintings. On the one hand, Krauss analyzes some pictures under a greenbergian perspective. On the other hand, she recovers duchampian affiliation to investigate Johns’ pictorial tactics. The question that arises runs as follows: to what extent is this second axis of analysis complementary to the first? The suggested answer is found in the play “Not I” by the playwright – and one of Johns’ partner – Samuel Beckett.
Keywords: Modernist Painting; Rosalind Krauss; Jasper Johns; Art Criticism; Contemporary art